Effectiveness of 1:1 speech and language therapy for older children with (developmental) language disorder. Issue 4 (18th November 2016) - Ebbels, Susan H.; Wright, Lisa; Brockbank, Sally; Godfrey, Caroline; Harris, Catherine; Leniston, Hannah; Neary, Kate; Nicoll, Hilary; Nicoll, Lucy; Scott, Jackie; Marić, Nataša
Abstract: Background: Evidence of the effectiveness of therapy for older children with (developmental) language disorder (DLD), and particularly those with receptive language impairments, is very limited. The few existing studies have focused on particular target areas, but none has looked at a whole area of a service. Aims: To establish whether for students with (developmental) language disorder attending a specialist school, 1:1 intervention with an SLT during one school term improves performance on targeted areas, compared with untreated control areas. Also, to investigate whether gender, receptive language status, autism spectrum disorder (ASD) status, or educational Key Stage affected their response to this intervention. Methods & Procedures: Seventy‐two students (aged 9–17 years, 88% of whom had receptive language impairments) and all speech and language therapists (SLTs) in our specialist school for children with Language Disorder, most of whom have DLD participated in this study over one school term. During this term, the SLTs devised pre‐ and post‐therapy measures for every student for each target they planned to treat 1:1. In addition, for each target area, a control measure was devised. The targets covered a wide range of speech, language and communication areas, both receptive and expressive. Post‐therapy tests were administered 'blind'. Outcomes & Results: During the term, SLTs and students worked 1:1 on 120 targets, the majority in the areas of expressive and receptive language. Targets and controls did not differ pre‐therapy. Significant progress was seen both on targets ( d = 1.33) and controls ( d = 0.36), but the targeted areas improved significantly more than the controls with a large and clinically significant effect size ( d = 1.06). There was no effect of language area targeted (targets improved more than their controls for all areas). Participants with versus those without receptive language difficulties, co‐occurring ASD diagnosis or participants in different educational Key Stages did not differ significantly in terms of the progress they made on target areas. Conclusions & Implications: Direct 1:1 intervention with an SLT can be effective for all areas of language for older children with (D)LD, regardless of their gender, receptive language or ASD status, or age. This adds to the relatively limited evidence base regarding the effectiveness of direct SLT intervention for school‐aged children with (D)LD and for children with receptive language impairments. If direct 1:1 intervention can be effective with this hard‐to‐treat group, it may well also be effective with younger children with (D)LD. Thus, direct SLT services should be available for school‐aged children with (D)LD, including older children and adolescents with pervasive difficulties.